A hierarchical p-hub center problem for perishable products using CPLEX method and origin-destination approach (2021)
The problem studied in this paper is the p hub center and the network structure is hierarchical and in three levels; where level one is for demand nodes, level two is for hub nodes, and level three is for central hubs. Central hubs have a complete network and hubs in the network have the capacity constraint. Given that the issue under consideration is for the purpose of transporting perishable goods, Such problems are often used in transportation systems in which customer response time is of great importance and sensitivity; Therefore, the objectives of the proposed model are to find the best location for hubs in the network as well as the best allocation of nodes to hubs so that network transportation costs are reduced and the maximum travel time between each pair of origin destination nodes is minimized. To evaluate the model, a numerical example with CAB dataset is introduced and to review and analyze the results, GAMS software with CPLEX solver is used. The results show that the discount coefficient of central hubs compared to the discount coefficient of second level hubs has the greatest impact on the cost of transportation and travel time.